Isosteric heat of adsorption for water adsorbed on ThO2 - Tsvia Ron; P. Schindler (CHIMIA)
The isosteric heat of adsorption for water on ThO2 was measured as a function of the surface coverage. The ΔHst-values referring to the formation of the second and third monolayer are smaller than the heat of liquefaction of pure water.